How much does aggregate demand travel across the Atlantic? - Ine Van Robays; Livio Stracca (European Central Bank (ECB), 2020)
We identify the spill-over of demand shocks between the world's two largest advanced economies; the US and the euro area. We estimate a Bayesian VAR with sign restrictions, using standard restrictions for the domestic impact of the shock but a novel approach to identify the geographic location of the shocks and rule out common shocks. For the latter, we use the relative performance of small open economies that are neighbors of the US and the euro area, respectively Canada and Sweden, in addition to restricting the relative effects on the US, the euro area and the rest of the world. We find that demand spill-overs of US and euro area demand shocks become smaller on average when imposing relative restrictions, while they become larger in periods which are well-known to be specific to the US (global financial crisis) or the euro area (euro area sovereign debt crisis). Our results are confirmed by running a "placebo test" where we replace the euro area with a small euro area economy, which should not have an independent effect on the US economy due to its small size.
Keywords: C5; F41; F44; 330; International spillovers; open economy; Bayesian VAR; sign restrictions